Vicious fun [videorecording (DVD)] - Villeneuve, James; Marsh, Evan; Goldfarb, Amber; Millen, Ari; Koechner, David, 1962- (Shudder, RLJE Films, 2022)
Joel, a caustic 1980's film critic for a national horror magazine, finds himself unwittingly trapped in a self-help group for serial killers. With no other choice, Joel attempts to blend in with his homicidal surroundings or risk becoming the next victim.